Special Competence for Preschool Teacher in 5.0 Era - Husnul Khotimah; Dewi Nur Suci (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
The role of the teacher will be replaced childhood in the learning proccess as a character reference. The onslaught of influence from social media and technological developments that are not unlimited in the 5.0 era forces teachers to continue upgrading their competencies and are even required to have special competencies. This study aims to examine what competencies must be possessed by Preschool teacher in this 5.0 era. This type of research locus in PAUD Rahmat, PAUD al-Irsyad al-Islamiyyah and PAUD al-Azhar Kediri. Some of the research instruments used were interview guides, observation, sheets and school documents which were then analyzed using the interactive analysis model  Miles and Huberman. The results of this research show that PAUD teachers do not only need four competencies as contained in the Permendiknas Republik Indonesia number 16 of 2007, but also need special competencies to collaboratie, namely counseling competence, an effort teachers in guiding their students to achieve self understanding and every information related to the surrounding environment.